THE RISK FACTORS AND BEHAVIORS ASSOCIATED WITH HOUSE DUST MITE-RELATED ALLERGIC RESPIRATORY DISEASES: A HOSPITAL-BASED STUDY - Jahja, Natalia Erica; Hikmah, Zahrah (The Indonesian Journal of Public Health, 2026)
Introduction: Allergic respiratory disease (ARD) affects 10-30% of the global population, especially children, and is frequently triggered by house dust mites (HDM). Gresik, a metropolitan area in East Java with high air pollution, contribute to an increased prevalence of ARD symptoms. Aim: This study aimed to identify risk factors and behaviours associated with HDM allergies in children, using a questionnaire-based approach. Methods: A cross-sectional survey was conducted from February to July 2023 at Petrokimia Gresik Hospital. Participants included children aged six months and older with chronic cough or rhinitis. HDM allergy diagnosis was confirmed via skin prick test (SPT) or specific immunoglobulin E (IgE) test only after excluding other differential diagnoses. Data on ARD symptoms and HDM-related risk factors were collected through a validated questionnaire and analyzed using descriptive, bivariate, and multivariate logistic regression model with significance set at p<0.05. Results: Of 344 eligible children, 261 completed the study. Children with HDM allergy (22.6%) were notably older (5.5 ± 2.5 years) compared to those without HDM allergy (4.5 ± 2.5 years; p=0.001). In the multivariable analysis, family history of atopy was independently associated with higher odds of HDM allergy (AOR 2.72; 95% CI 1.27–5.79; p = 0.010), whereas increasing age was associated with lower odds (AOR 0.989; 95% CI 0.980–0.998; p = 0.013). Conclusion: Family history of atopy showed a stronger association with HDM allergy, while increasing age was inversely associated. Environmental factors were not significant after adjustment. However, multicentre studies are essential to validate these findings.